-15+(-12)+(-21)=

Simple and best practice solution for -15+(-12)+(-21)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15+(-12)+(-21)= equation:


Simplifying
-15 + (-12) + (-21) = 0
-15 + -12 + (-21) = 0
-15 + -12 + -21 = 0

Combine like terms: -15 + -12 = -27
-27 + -21 = 0

Combine like terms: -27 + -21 = -48
-48 = 0

Solving
-48 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7x-2=-4x-5.4 | | n*5+8=9n | | (0.3+2x)(0.3+2x)=3.266 | | 5x+15/5=35+x | | -6x=7x^2-x-12 | | 7x+28-10=0 | | -11x^2-8x+3=0 | | 6n-75=n | | (0.3+2x)(0.3+2x)=3.27 | | v/6=3 | | 25-10x=7+4x | | 24-5*(3-3x)=-51 | | y-3.25=8.5 | | 5-4*(5+4x)=1 | | 3x^2-7x+11=0 | | P^2-12+9=0 | | x-1/7=6.4 | | 2x+(-10+4x)+13=51 | | m-2.4+2.4=5.3+2.4 | | 12+5*(4-x)=32 | | 2-(9-4x)+10=7 | | c=(5d-2)/(9+7d) | | 3y=81x | | 36x^2-24x=-4 | | 2x+(6+2x)+14=36 | | 15+5*(5+3x)=70 | | 10=-x^2+7x | | 8x-(5x+9)+16=-2 | | 4x+(4x+3)+7=34 | | x-2/3+2/3=6+2/3 | | 3(6-n)=4 | | 2x+5=79-10x |

Equations solver categories